Modular Programming: Novice Misconceptions - Madison, Sandra; Gifford, James (Journal of research on technology in education, 2002)
This study explored the parameter-related misconceptions of two college students enrolled in an introductory programming course. Both students appeared to conceive a direct procedure-to-procedure linkage, with the connection being forged by identically named formal parameters. Throughout the semester, both students were able-by making apparently innocuous adjustments to formal parameter lists-to construct correctly functioning modular programs. They were also able to correctly answer parameter-related test questions when the questions did not provoke a conflict with their fundamental misconception of the parameter process. Therefore, the misconceptions were concealed from the instructor and perhaps from the students themselves. This article discusses the results of the study within the constructivist framework and suggests implications for instruction.